Intervenção não-farmacológica via telefone na sobrecarga decuidadoras de pacientes com demência : ensaio clínico randomizado - Pereira, Andressa Hermes (2024)
Theoretical basis: Dementia is a clinical syndrome that causes cognitive impairments and compromises the functionality and independence of the elderly, usually starting at age 65. It also profoundly affects the family, especially female caregivers. These caregivers face a series of challenges that compromise their physical and mental health, such as emotional and physical overload, depressive and anxious symptoms, social isolation, financial pressure, and decreased quality of life. The caregiving responsibilities, which include assisting with mobility, personal hygiene, and medication management, can be extremely exhausting and lead to significant burnout. To mitigate these negative effects, it is essential that caregivers receive adequate support, such as support groups, education and training, professional assistance, and self-care, including regular medical appointments, exercise, and time for enjoyable activities. Additionally, a support network of family and friends is crucial to provide the necessary help, contributing to a comprehensive approach that benefits both the patient and the caregivers. Objective: This research aims to evaluate the effectiveness of a psychoeducation and support protocol conducted by telephone in reducing the burden on caregivers of patients with dementia. Methods: Randomized, parallel, partially blinded clinical trial to evaluate the effectiveness of a telephone psychoeducation and support protocol in reducing the burden on caregivers of patients with dementia. The primary outcome was the difference in caregiver burden between week 1 (T0), week 8 (T1), and week 16 (T2), measured by the Zarit Burden Interview (ZBI). Secondary outcomes included depressive and anxious symptoms, quality of life, neuropsychiatric symptoms in the patient, the impact of these symptoms on the caregiver, and patient functionality. The intervention group received 8 psychoeducation and support phone calls between T0 and T1, while the control group continued with usual health care and received a booklet with information about the disease. Results: A total of 128 participants with a mean (SD) age of 55.3 ± 11.1 years in the intervention group and 53.1 ± 11.1 years in the control group were included. Caregivers had a mean (SE) score of 31.5 (1.8) points in the intervention group and 31.0 (1.7) in the control group at baseline assessment of the primary outcome. After 8 weeks, the intervention group had 29.7 (2.1) and the control group had 31.3 (1.93) points, while at 16 weeks, the intervention group showed 31.9 (2.42) and the control group 31.4 (1.98) in caregiver burden variable. Conclusion: The intervention showed a decrease in the score levels of burden between the initial assessment and after 8 weeks (T0 and T1) when compared to the average score in the control group. However, these differences were not statistically significant when analyzed. Further studies aiming to investigate different intervention models should be pursued.